Comparison of Mortality Outcomes in Acute Myocardial Infarction Patients With or Without Standard Modifiable Cardiovascular Risk Factors - Sia, Ching-Hui; Ko, Junsuk; Zheng, Huili; Ho, Andrew Fu-Wah; Foo, David; Foo, Ling-Li; Lim, Patrick Zhan-Yun; Liew, Boon Wah; Chai, Ping; Yeo, Tiong-Cheng; Yip, James W. L.; Chua, Terrance; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Acute myocardial infarction (AMI) cases have decreased in part due to the advent of targeted therapies for standard modifiable cardiovascular disease risk factors (SMuRF). Recent studies have reported that ST-elevation myocardial infarction (STEMI) patients without SMuRF (termed “SMuRF-less”) may be increasing in prevalence and have worse outcomes than “SMuRF-positive” patients. As these studies have been limited to STEMI and comprised mainly Caucasian cohorts, we investigated the changes in the prevalence and mortality of both SMuRF-less STEMI and non-STEMI (NSTEMI) patients in a multiethnic Asian population. Methods We evaluated 23,922 STEMI and 62,631 NSTEMI patients from a national multiethnic registry. Short-term cardiovascular and all-cause mortalities in SMuRF-less patients were compared to SMuRF-positive patients. Results The proportions of SMuRF-less STEMI but not of NSTEMI have increased over the years. In hospitals, all-cause and cardiovascular mortality and 1-year cardiovascular mortality were significantly higher in SMuRF-less STEMI after adjustment for age, creatinine, and hemoglobin. However, this difference did not remain after adjusting for anterior infarction, cardiopulmonary resuscitation (CPR), and Killip class. There were no differences in mortality in SMuRF-less NSTEMI. In contrast to Chinese and Malay patients, SMuRF-less patients of South Asian descent had a two-fold higher risk of in-hospital all-cause mortality even after adjusting for features of increased disease severity. Conclusion SMuRF-less patients had an increased risk of mortality with STEMI, suggesting that there may be unidentified nonstandard risk factors predisposing SMuRF-less patients to a worse prognosis. This group of patients may benefit from more intensive secondary prevention strategies to improve clinical outcomes.